Adopting Inflation Targeting : Practical Issues for Emerging Market Countries - Zelmer, Mark (Occasional Papers; Occasional Paper, 2000)
This report on Adopting Inflation Targeting describes the trade-offs raised in the formulation of an inflation targeting framework and states the approaches to these trade-offs used by inflation targeting countries. The inherent differences discussed in this report between the six emerging market inflation targeting countries-Brazil, Chile, the Czech Republic, Israel, Poland, and South Africa-and other emerging market countries may shed some light on the preferred starting point and conditions for inflation targeting. Most central banks in emerging market countries have taken important organizational steps to enhance their capacity to apply greater judgment and foster transparency and accountability. These steps can be particularly challenging for emerging market central banks that have traditionally operated with controls and regulations and have been reluctant to communicate their policy intentions and economic outlooks. During the transition to full-fledged inflation targeting, several emerging market countries have confronted the challenge of dis-inflating to the long-run inflation objective.